Influencia del uso de crédito tributario en las empresas comerciales. - Collaguazo Collaguazo, Christian Ivan (My University, 2020)
The Internal Revenue Service (SRI) as a tax collection organization foresees concurrence with the law for the collection of taxes. This work will refer to the Value Added Tax (VAT), which is an indirect tax that the taxpayer must pay for the acquisition or provision of a good or service taxed at a 12% rate. The objective is based on determining the influence of the use of tax credit in commercial companies, the results will be presented in quantitative terms. Therefore, the collection of Value Added Tax directly contributes to public spending and commercial companies that are dedicated to the sale of goods and services with rates 12% and 0%, will be entitled to tax credit of the proportionate share for the VAT paid Likewise, the difference that occurs may be sent to the expense.
El Servicio de Rentas Internas (SRI) como organización recaudadora de tributos prevé concurrencia con la ley para el recaudo de los impuestos. El presente trabajo hará referencia sobre el Impuesto al Valor Agregado (IVA), el cual es un impuesto indirecto que el contribuyente debe pagar por la adquisición o prestación de un bien o servicio gravado con tarifa 12%. El Objetivo se basa en determinar la influencia del uso del crédito tributario en las empresas comerciales, los resultados estarán presentados en términos cuantitativos. Por lo tanto, la recaudación del Impuesto al Valor Agregado aporta directamente al gasto público y a la empresas comerciales que se dedican a la venta de bienes y servicios con tarifas 12% y 0%, tendrán derecho crédito tributario de la parte proporcional por el IVA pagado, así mismo la diferencia que se produce podrán enviarlo al gasto.
Keywords: TRIBUTOS; IMPUESTO AL VALOR AGREGADO; CRÉDITO TRIBUTARIO